Remapping Student Research Maps Zakat and Waqf Management Study Programme Sunan Ampel Surabaya State Islamic University - Mustofa, Mustofa; Adi Putranto, Hanafi (Management of Zakat and Waqf Journal (MAZAWA), 2024)
: this study aims to construct student research mapping in the science of zakat and waqf management at Sunan Ampel State Islamic University Surabaya. The construction of research maps is needed to prepare graduates who are visionary, contributive and competitive in the future. The research method is a case study. The variables used are research subjects, study topics and research places. The research subject is the final project of students in the Zakat and Waqf Management Study Programme at Sunan Ampel Surabaya State Islamic University in the span of 2015 to 2022. The results showed that the majority of research on zakat and waqf used qualitative research methods, the themes raised were related to amil zakat and nadzir wakaf. There are three influencing variables, namely: scientific inclination, liking logic and criticism, disliking statistical figures and being elastic.